Strategi Pengembangan Usahatani Jagung (Zea Mays L.) Untuk Meningkatkan Produktivitas di Kecamatan Watang Pulu, Kabupaten Sidenreng Rappang - Munawarah Munawarah; Fadillah Nurdin; Nurfadillah Nurfadillah; Sri Bulan (Universitas Galuh, 2026)
Corn is a fairly important necessity for human life and is the second most important food crop commodity after rice. One of the corn production centers is located in Watang Pulu District. Corn production in this area draws government attention. Although corn is one of the superior commodities in Watang Pulu District, there are still several urgent issues faced by corn farmers, including relatively low production levels, limited capital for corn farming, pest and disease attacks that lead to increased maintenance costs and decreased production yields, continued use of traditional planting systems, and market corn prices that tend to be unstable, directly affecting corn farmers' income. The purpose of this research is to identify the internal and external factors of corn farming and to formulate development strategies for corn farming to increase corn productivity. The methods used in this study are qualitative and quantitative methods. Primary and secondary data collection was carried out through FGDs, surveys, and in-depth interviews with corn farmer stakeholders. The data analysis used is SWOT Analysis. The research location was selected purposively, considering that Watang Pulu District is an area with the largest potential corn plantation land in Sidenreng Rappang Regency, South Sulawesi. The research was conducted over five months (May – September 2025) with the conclusion that the strategy to be developed is the ST diversification strategy (cell 2). This strategy represents the condition of corn farming faced with various threats. Nevertheless, corn farming has strengths that can be utilized. The strategy implemented focuses on how to use the existing strengths and minimize threats to develop corn farming in order to increase productivity in Watang Pulu District.Keywords: External Factors, Internal Factors, Corn, Development, Strategy.